Implementasi kansei engineering dalam pengembangan kemasan minuman kopi ready to drink - Novi Purnama Sari; Zulkarnain Zulkarnain; Verian Ardi Muzaki; Yuni Dita Meilani (AGROINTEK, 2024)
Currently, the coffee business is becoming a trend in the market. So determining the right packaging design is an important thing to plan. The product development method that has been proven optimal is Kansei engineering. This study compares the results of developing ready-to-drink coffee packaging (cold and hot) with the Kansei engineering method based on consumer emotions. Kansei engineering is a powerfull method that can translate consumer needs into design elements. This method is supported by several multivariate statistical methods and artificial intelligence methods. The results obtained for a cold coffee drink are 25 packaged samples and 30 Kansei words, while 20 samples and 20 Kansei words for a hot coffee drink. The packaging design concepts for a cold coffee drink obtained from Kansei word extraction using the principal component analysis (PCA) method are "standard-attractive" and "unique-general." While the packaging design concepts for a hot coffee drink using the term frequency-inverse document frequency (TFIDF) method and factor analysis are "premium-modern" and "natural-elegant." based on the quantification theory type-1 (QTT1) method, the packaging design elements from the “unique-general” concept for a cold coffee drink are obtained, namely: wooden packaging lids with distinctive bottle mouths, The neck of the pack is straight and short, The packaging body resembles a sake bottle, the bottom of the pack is slightly concave in the middle, plastic packaging materials, and uninformative label design. While the “premium-modern" concepts for a hot coffee drink using the rough set method has packaging elements, namely, there is a sleeve or none at all, with a reclosable hole top, flat bottom, rounded/convex body, direct print decoration, and with decorative fonts. In contrast, the “natural-elegant” concept has packaging elements without reclosable holes, straight body, paper cup material, light colors, no image, and decorative fonts.the emotional interpretation of the object strongly influences the application of Kansei engineering.